Injectable Autocatalytic Hydrogel Triggers Pyroptosis to Stimulate Anticancer Immune Response for Preventing Postoperative Tumor Recurrence - Zhiping Rao; Yutong Zhu; Zhuang Chen; Yi Luo; Zuo Yang; Weijing Liu; Chaoqiang Qiao; Yuqiong Xia; Peng Yang; Dong‐Man Ye; Zhongliang Wang (Advanced Science)
Abstract Modulating immunosuppression while eliminating residual microscopic tumors is critical for inhibiting the postoperative recurrence of triple‐negative breast cancer (TNBC). Although immunotherapy has shown potential in achieving this goal, due to multiple immunosuppression and poor immunogenicity of apoptosis, a satisfactory anti‐recurrence effect still faces the challenge. Herein, an injectable hydrogel‐encapsulated autocatalytic copper peroxide (CP@Gel) therapeutic platform is designed and combine it with the clinical‐grade DNA methyltransferase inhibitor decitabine (DAC) to effectively inhibit TNBC growth and postoperative recurrence via pyroptosis, killing residual cancer cells that bypass apoptosis resistance while also improving immunogenicity and modulating immunosuppression to achieve an intense anti‐tumor immune response. Following injection of the CP@Gel, the sustained release of CP leads to the autocatalytic generation of reactive oxygen species, resulting in caspase‐3 activation, and the pre‐administered DAC inhibits the methylation of Gsdme to elevate the GSDME protein levels, leading to intense pyroptosis and anti‐tumor immune responses. The in vivo results show a 67% elimination of local tumor recurrence via treatment with DAC+CP@Gel, suggesting the successful integration of sustained drug release with autocatalysis and epigenetic modification. The results thus suggest great potential for pyroptosis‐based and injectable hydrogel‐aided strategies for preventing the postoperative recurrence of TNBC.